Systemic immune-inflammation index and in-stent restenosis in patients with acute coronary syndrome: a single-center retrospective study - Xie, Feng; Yu, Zuozhong; Xiong, Yurong; Wu, Zhijian; Wu, Yanqing (European journal of medical research, 2024)
Background In-stent restenosis (ISR) has been shown to be correlated with inflammation. This study aimed to examine the relationship between systemic immune-inflammation index (SII, an innovative inflammatory biomarker) and ISR in acute coronary syndrome (ACS) patients after drug-eluting stent (DES) implantation. Methods Subjects who were diagnosed with ACS and underwent DES implantation were enrolled retrospectively. All individuals underwent follow-up coronary angiography at six to forty-eight months after percutaneous coronary intervention (PCI). SII was defined as [(platelet count × neutrophil count)/lymphocyte count], and Ln-transformed SII (LnSII) was carried out for our analysis. Multivariate logistic regression analysis was employed to assess the association between LnSII and DES-ISR. Results During a median follow-up period of 12 (11, 20) months, 523 ACS patients who underwent follow-up angiography were included. The incidence of DES-ISR was 11.28%, and patients in the higher LnSII tertile trended to show higher likelihoods of ISR (5.7% vs. 12.1% vs. 16.0%; P = 0.009). Moreover, each unit of increased LnSII was correlated with a 69% increased risk of DES-ISR (OR = 1.69, 95% CI 1.04–2.75). After final adjusting for confounders, a significant higher risk of DES-ISR (OR = 2.52, 95% CI 1.23–5.17) was found in participants in tertile 3 (≥ 6.7), compared with those in tertiles 1–2 (< 6.7). Subgroup analysis showed no significant dependence on age, gender, body mass index, current smoking, hypertension, and diabetes for this positive association (all P for interaction > 0.05). Conclusion High levels of SII were independently associated with an increased risk of DES-ISR in ACS patients who underwent PCI. Further prospective cohort studies are still needed to validate our findings.